2021
DOI: 10.1038/s41398-020-00993-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychological responses among nurses caring for patients with COVID-19: a comparative study in China

Abstract: Frontline healthcare nurses devoted themselves to deal with the outbreak of COVID-19, saving many lives. However, they are under incredible unknown psychological pressures with a considerable risk of infection. In this study, a self-administered questionnaire was used to survey 593 frontline nurses in Wuhan City and non-Hubei provinces for psychological responses from March 1 to March 10, 2020. Compared with nurses outside Hubei Province, those working in Wuhan were more likely to feel physically and mentally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The effect of COVID-19 as well as its limitation rules on the researched group has been investigated in a number of studies (McKune et al, 2021;Qin et al, 2021;Błaszczyk et al, 2022). Multivariable logistic regression models were used in many research to: (i) examine the possible risk factors defined as selfemotional problems (Ren H. et al, 2021) and (ii) compare the impact of COVID-19 assessments (Gomathi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of COVID-19 as well as its limitation rules on the researched group has been investigated in a number of studies (McKune et al, 2021;Qin et al, 2021;Błaszczyk et al, 2022). Multivariable logistic regression models were used in many research to: (i) examine the possible risk factors defined as selfemotional problems (Ren H. et al, 2021) and (ii) compare the impact of COVID-19 assessments (Gomathi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of studies have been conducted to examine the impact of COVID-19 and its restriction policies on the studied population [ 6 , 7 , 8 ]. Specifically, multivariable logistic regression analyses were adopted in various studies to: (i) identify the correlations of mental health with other factors [ 9 , 10 , 11 ], such as sociodemographic features [ 4 , 12 , 13 , 14 ] and/or school aspects [ 14 ] or health behaviors [ 15 ], mostly on university students [ 16 , 17 , 18 ]; (ii) assess the prevalence and the risk factors associated with self-reported psychological distress [ 19 ]; and (iii) evaluate the effects of COVID-19 measures upon the mental health of children and adolescents, with or without pre-existing diagnoses [ 20 ]. Binomial or binary logistic regression analysis was used to: (i) identify sleeping problems of adolescents and young adults (12–29 years) during the pandemic [ 21 , 22 ]; (ii) assess depression and anxiety amongst university students [ 23 ]; and (iii) examine the prevalence of anxiety among children and the possible association to COVID-19 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, loss of appetite was observed. Previous study showed that nurses in Wuhan city had higher score in poor appetite or overeating than nurses in other cities (Ren et al, 2021 ). These health issues were associated with the negative psychological experiences and might further the conditions.…”
Section: Discussionmentioning
confidence: 93%